PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA ( Studi Pada Bank Tabungan Pensiunan Nasional Kantor Cabang Semarang ) - Yusuf Hazmi Anugrah; Apriatni Endang Prihatini; Sendhang Nurseto (Jurnal Ilmu Administrasi Bisnis, 2013)
PT. Bank BTPN Branch Semarang is one of the company's core banking business on the retirees, especially in the distribution of Pension Credit. To face tight competition, companies are required to always improve the quality of performance through improved employee satisfaction. Low job satisfaction will result in high employee absenteeism or employee discharge. In order to improve the job satisfaction of employees needed good leadership and a supportive working environment. The purpose of this study is to investigate and examine the effect of leadership and work environment on employee job satisfaction BTPN Semarang branch office. This research uses explanatory research approach of 32 respondents that taken with saturated sampling method. Collection techniques using questionnaires, interviews and documentation. Data were analyzed analysis using linear regression analysis. Based on the results of analysis of leadership variables positive effect on job satisfaction variable by 19%. Variable work environment has positive effect on the job satisfaction variable by 19.8%. Leadership and work environment variables have a significant effect of 35.3%. Good leadership and a supportive work environment that will increase employee job satisfaction. Advice that can be given to the company, the company should rethink about welfare of its employees. The companies should rethink about leaders how can nurturing employees. Companies should rethink the physical condition of the work environment, especially on the frequent changes in layout. Which in turn can increase the productivity of employees in line with the increase in employee satisfaction.